An image of a woman in a sports advertisement - Kończak, Jarosław (Journal of Education, Health and Sport, 2022)
Introduction. In 1987, sport was known in the literature as an area representing a traditional male power, strength and violence. In 2020, women’s sport became recognized as the mainstream, which only confirmed similar conclusions made over the past years. One of the challenges in the area of sport over the next years was women’s sport activation and reaching them through sponsorship communication. This has been facilitated, inter alia, by the development of women’s sport and its marketing potential. The study aims to present the image of a woman in marketing communication based on sports motives. The selected aspects subjected to analysis will help to define the role of women in advertising sports communication and verify the declarations of the companies that achieve their goals using this level of communication. Another aim is to investigate whether the belief in the feminization of sports fandom and involvement of women in the fan culture finds confirmation in advertising. Method. The author has analysed selected TV, cinema and internet advertising campaigns (audio-video format) containing sports accents. Communications of 1,270 films representing 254 brands was analysed. The analysis covered seven different areas: characters, image and product advertising, share of sports disciplines, sports accessories used, the woman’s attitude, an area of the sports involvement, and the values presented. Results. The analysis allowed to obtain an image of a woman being aware of her strength, who can derive great joy from sport. She believes that this is an important and popular area which has a beneficial effect on health and guarantees a shapely figure and great fun. She is a woman being aware of a number of values that come with sport, as she can see how much she benefits in the spiritual, physical and emotional dimensions. However, she feels her emotions much more often through the way to success and fighting for the position of a leader rather than cheerleading.